Designing Sneakers as A Medium to Support Teaching and Learning Speaking - Rizky Kurniawan (Journal of English Education Program, 2023)
The goal of this study was to create the board game Sneakers as a teaching and learning tool for speaking and to determine whether or not eleventh-grade students would find it useful and appropriate for that purpose. Card games and board games make up the medium. The teacher and students at the school utilized a book, and the materials were obtained from the internet. The three parts of the process—Analyze, Design, and Develop—were derived from Branch's (2009) ADDIE Model. Students require dynamic, visually appealing media during the analysis phase to participate in the teaching and learning process. The media's structure, as well as all of the elements that were increasingly its primary focus, were all covered throughout the design process. The development process was carried out to create the fundamental components of the media, such as the game's rules. Sneakers are frequently employed as a medium to promote or facilitate the teaching and learning of speaking for the eleventh-grade students at SMA Muhammadiyah 2 Pontianak, according to the evaluation's findings